Squamous Cell Carcinoma of the Suprapubic Cystostomy Tract With Bladder Involvement - Chung, Jae Min (The Korean Urological Association, 2013)
Herein we report a case of a squamous cell carcinoma of a well-healed suprapubic cystostomy tract scar involving the bladder mucosa in a 56-year-old man. He presented with a spontaneous suprapubic urinary leak from a suprapubic cystostomy tract scar. He had a history of urethral stricture and failed urethroplasty. Preoperative cystoscopy suggested a bladder mass. Transurethral biopsy of the bladder mass revealed a squamous cell carcinoma confined to the suprapubic cystostomy tract involving the bladder mucosa. The patient died 6 months after the start of radiation therapy after lung metastasis and pneumonia.